Diseño de un sistema fotovoltaico tipo on grid que suplirá el 60% de la carga eléctrica total de la empresa incoel s.a.s ubicada en la ciudad de Bogotá - Diaz Reyes, Julian; Giraldo Orjuela, Smith (Universidad Antonio Nariño, 2021)
We wish to take advantage of solar energy through the design of a photovoltaic system to reduce electricity billing costs and make a contribution to the reduction of the carbon footprint generated by the company Ingeniería y Construcción Eléctrica INCOEL S.A.S. Due to these conditions, the current legal regulations established by RETIE, NTC 2050, CREG, UPME and the network operator (Enel Codensa) must be taken into account. The latter will approve the electrical project, which will have a bidirectional meter that will record the energy consumed and the energy injected into the network, thus generating a retroactive payment to the company for the production of electrical energy. This project will be carried out on the company's roof located in the city of Bogotá. A survey of information related to the internal and external electrical network infrastructure was carried out, an analysis of the loadability study was presented and once all the variables that determined the capacity of the photovoltaic system were verified, a system with nine 455 W panels was designed, for an annual energy production of 6104 kWh per year, which would supply up to 85.46% of the total electrical load currently consumed by the company